Implementasi Program Sekolah Ramah Anak melalui Sosialisasi Anti-Perundungan di SMA N 1 Kersana Brebes - Muh Sahidun; Faizal Yudhi Nugroho; Muamar Riza Pahlevi; Fajar Sigit Kusumajaya (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
Bullying in secondary schools is a serious issue that affects students’ psychosocial well-being and academic achievement, and significantly disrupts the learning climate and the quality of social relationships among students. This community service activity aimed to implement the Child-Friendly School Program through anti-bullying socialization at SMA N 1 Kersana in order to enhance the understanding and commitment of all school members in creating a safe, inclusive, and sustainable learning environment. The method employed a participatory approach, including needs assessment, interactive socialization sessions, focus group discussions, case simulations, and structured evaluation using pre-test and post-test instruments. The results indicated a 23% increase in participants’ understanding based on the comparison of scores before and after the intensive implementation of the program. Furthermore, a “Bullying-Free School” declaration was established along with a plan to strengthen the Violence Prevention and Handling Team as a more systematic sustainability strategy. These findings confirm that participatory-based socialization effectively reinforces the implementation of the Child-Friendly School Program and fosters a safe, inclusive, sustainable, and responsive school culture that supports students’ positive character development.